Contribution of CFTR to Alveolar Fluid Clearance by Lipoxin A4 via PI3K/Akt Pathway in LPS-Induced Acute Lung Injury. (16th May 2013) - Yang, Yi; Cheng, Yang; Lian, Qing-Quan; Yang, Li; Qi, Wei; Wu, De-Rong; Zheng, Xia; Liu, Yong-Jian; Li, Wen-Juan; Jin, Sheng-Wei; Smith, Fang Gao
Abstract : The lipoxins are the first proresolution mediators to be recognized and described as the endogenous "braking signals" for inflammation. We evaluated the anti-inflammatory and proresolution bioactions of lipoxin A4 in our lipopolysaccharide (LPS-)induced lung injury model. We demonstrated that lipoxin A4 significantly improved histology of rat lungs and inhibited IL-6 and TNF- α in LPS-induced lung injury. In addition, lipoxin A4 increased alveolar fluid clearance (AFC) and the effect of lipoxin A4 on AFC was abolished by CFTR inh - 172 (a specific inhibitor of CFTR). Moreover, lipoxin A4 could increase cystic fibrosis transmembrane conductance regulator (CFTR) protein expression in vitro and in vivo . In rat primary alveolar type II (ATII) cells, LPS decreased CFTR protein expression via activation of PI3K/Akt, and lipoxin A4 suppressed LPS-stimulated phosphorylation of Akt. These results showed that lipoxin A4 enhanced CFTR protein expression and increased AFC via PI3K/Akt pathway. Thus, lipoxin A4 may provide a potential therapeutic approach for acute lung injury.